Legal Implications of Underhand Agreements Between Hospitals and Medical Device Distributors - Mekarsari, Septi Wahyuning; Prayitno, Ahmad Hadi; Laksana, Andri Winjaya (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
Procurement of medical devices is an important part in supporting health services in hospitals. In practice, cooperation between hospitals and distributors of medical devices is often stated in the form of private agreements without involving a notary. This study aims to analyze the legal implications of private agreements in the event of a breach of contract between hospitals and distributors of medical devices, both from the perspective of civil law and health law, and to provide legal recommendations as a reference for dispute resolution. The type of research used is sociological juridical research with a case study at RSAU dr. Yuniati Wisma Karyani Natuna. The research specifications are descriptive analysis, the types of data used are primary data, secondary data, primary legal materials, secondary legal materials and tertiary legal materials, then the data collection method is by interviewing health workers at RSAU dr. Yuniati Wisma Karyani Natuna, and the analysis method in this study is qualitative analysis. The results of the study indicate that private agreements still have binding legal force as long as they meet the legal requirements of the agreement as regulated in Article 1320 of the Civil Code. However, the agreement has limitations in terms of evidentiary power compared to authentic deeds. In the event of a breach of contract, the injured party has the right to demand fulfillment of the contractual obligations, compensation, cancellation of the agreement, or transfer of risk. From a health law perspective, a breach of contract has the potential to compromise the quality of healthcare services and patient safety, thus requiring the hospital to retain legal responsibility for the provision of healthcare services. Therefore, this study recommends that cooperation agreements be drawn up in the form of an authentic deed or at least legalized.